2018
DOI: 10.1016/j.tra.2018.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Have Asian airlines caught up with European Airlines? A by-production efficiency analysis

Abstract: This paper extends previous approaches to meta-efficiency measures by incorporating meta-frontiers using good-output, bad-output and by-production efficiencies to compare European and Asian airlines. We also examine whether the heterogeneity in environmental regulatory standards between these regions has emboldened Asian airlines to be less eco-friendly and/or more market-share seeking. We find that the environmental performance of European airlines improved continuously between 2007 and 2013, unlike their com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…Asia-Pacific airlines are an important collective force in the international aviation market, accounting for a quarter of the total global air passenger demand and two-fifths of the global air cargo demand [19]. Boeing predicts that Asia will account for half of global aviation demand growth [20].…”
Section: Asian Airlinementioning
confidence: 99%
“…Asia-Pacific airlines are an important collective force in the international aviation market, accounting for a quarter of the total global air passenger demand and two-fifths of the global air cargo demand [19]. Boeing predicts that Asia will account for half of global aviation demand growth [20].…”
Section: Asian Airlinementioning
confidence: 99%
“…Hu et al (2017) used a DEA model and bootstrapping to analyze the operational efficiencies in 15 ASEAN airlines from 2010 to 2014 and found that the airlines had low efficiency, slightly better operating cost efficiency, and higher available seat efficiency. Arjomandi et al (2018) considered undesirable output (CO 2 emissions) in a meta‐DEA model to compare the efficiencies in 15 Asian airlines and eight European airlines from 2007 to 2013 and found that the environmental efficiencies in the European airlines were better than in Asian airlines, but that some Asian airlines had leading technologies. Ling et al (2018) used a Malmquist index to estimate the total factor productivity of five national airlines—Garuda Indonesia, Malaysian Airlines, Philippine Airlines, Singapore Airlines, and Thai Airways International—in five ASEAN countries from 2007 to 2013, finding that Philippine Airlines had the best efficiency and Malaysian Airlines was the least efficient.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Regarding input variables, three inputs were chosen, namely full-time equivalent employees, fuel consumption, and available seat miles (ASMs). The variable of labor has been commonly used as input in efficiency evaluation in the airline industry (Assaf and Josiassen, 2012;Merkert and Williams, 2013;Yu et al, 2016;Chang and Yu, 2014;Merkert and Pearson, 2015;Saranga and Nagpal, 2016;Cao et al, 2015;Arjomandi et al, 2018;Barros and Wanke, 2015;Kottas and Madas, 2018). Fuel presents one of the most critical materials for an airline operation.…”
Section: Data and Variables Selectionmentioning
confidence: 99%
“…The popularity of DEA as a powerful tool for assessing efficiency can be explained by its ability to handle multiple inputs and outputs and no presumption of production form (Lampe and Hilgers, 2015). Given the superiority of DEA over other methods, it has been widely applied in analyzing the efficiency of the aviation sector (for instance, see comprehensive literature review of Yu et al, 2017;Arjomandi et al, 2018;Cui et al, 2016;Kottasa and Madas, 2018).…”
Section: Introductionmentioning
confidence: 99%